The association between the years and modes of sports training and levels of moral competence across eleven sports - Małgorzata Bronikowska; Michał Bronikowski (Physical Education of Students, 2024)
Background and Study Aim. Research on moral competency in sports is rare, and findings are inconsistent. These findings point to moral development as a multifaceted and complex process. This process is mediated by various life situations and dilemma choices. Sport can play a crucial role in this area with its often ‘role-taking’ experience and confrontations with personal moral standards. This study aimed to analyze the relationship of competency levels and sport experience across different sports.